A monoamine oxidase B inhibitor ethyl ferulate suppresses microglia-mediated neuroinflammation and alleviates ischemic brain injury - Zou, Xinxin; Gao, Shenghan; Li, Jiangnan; Li, Chenggang; Wu, Chuyu; Cao, Xiang; Xia, Shengnan; Shao, Pengfei; Bao, Xinyu; Yang, Haiyan; Liu, Pinyi; Xu, Yun (Frontiers in Pharmacology, 2022)
Microglia are the resident macrophages in the brain, which play a critical role in post-stroke neuroinflammation. Accordingly, targeting neuroinflammation could be a promising strategy to improve ischemic stroke outcomes. Ethyl ferulate (EF) has been confirmed to possess anti-inflammatory properties in several disease models, including acute lung injury, retinal damage and diabetes-associated renal injury. However, the effects of EF on microglial activation and the resolution of post-stroke neuroinflammation remains unknown. Here, we found that EF suppressed pro-inflammatory response triggered by lipopolysaccharide (LPS) stimulation in primary microglia and BV2 cell lines, as well as post-stroke neuroinflammation in an in vivo transient middle cerebral artery occlusion (tMCAO) stroke model in C57BL/6 mice, consequently ameliorating ischemic brain injury. Furthermore, EF could directly bind and inhibit the activity of monoamine oxidase B (MAO-B) to reduce pro-inflammatory response. Taken together, our study identified a MAO-B inhibitor, Ethyl ferulate, as an active compound with promising potentials for suppressing post-stroke neuroinflammation.